MODERN APPROACHES TO INFECTION PREVENTION AFTER UTERINE ARTERY EMBOLIZATION IN UTERINE MYOMA - Ющенко, Марина Анатольевна; Мозес, Вадим Гельевич; Рудаева, Елена Владимировна; Елгина, Светлана Ивановна; Мозес, Кира Борисовна; Рыбников, Сергей Валерьевич; Центер, Яэль (Mother and Baby in Kuzbass, 2023)
Information was searched for PubMed, Scopus, Webof-science, RSCI databases using the following keywords: infection prevention, uterine artery embolization, uterine myoma, etiology, pathogenesis, diagnosis, treatment, without language restrictions. For the analysis, 34 sources with full access to the text were selected, 50 % of which were published within the last five years, and 90 % within the last three years. The criteria for excluding sources were low information content and outdated data. Uterine artery embolization (UAE) is an effective and safe procedure with a low overall incidence of postoperative uterine infections (
Keywords: infection prevention; uterine artery embolization; uterine myoma